Research for City Practice. Issue 1 (2nd January 2017) - Grant, Marcus; Brown, Caroline; Caiaffa, Waleska T.; Capon, Anthony; Corburn, Jason; Coutts, Chris; Crespo, Carlos J.; Ellis, Geraint; Ferguson, George; Fudge, Colin; Hancock, Trevor; Lawrence, Roderick J.; et al.
CITY KNOW-HOW: Planetary health and human health are influenced by city lifestyles, city leadership, and city development. Changing the trajectory requires concerted action, and the journal Cities & Health journal is dedicated to supporting the flow of knowledge, in all directions to help make this happen. We are dedicated to supporting communication between researchers, practitioners, policy-makers, communities and decision-makers in cities. The aim of the City Know-how section of the journal is to make research accessible to all, explaining the key messages to and for city leaders, communities and all those professions involved in city policy and practice. In response we would like to hear more about research priorities from those most closely connected with supporting health and health equity through everyday urban lives.